The Influence of Oligarchy on Southeast Asian Power Structures: : A Critical Analysis - Jahan, Munira (The Jahangirnagar Review, 2025)
Oligarchy has been present in various political systems, including democracies and autocracies. The policies of oligarchs have often influenced the political and economic landscapes of both developed and developing countries. Several factors have contributed to the rise of oligarchy in the region, including colonial legacies, constitutional monarchies, one-party dominance, family-led leadership, bureaucratic governance, and transitional democracy. Within this context, Southeast Asia has experienced significant economic growth over the past few decades, which has also influenced the development of oligarchic structures. What factors contribute to the political power of oligarchs in Southeast Asian nations? What strategies do these oligarchs employ to exert influence over political processes and outcomes? The study posits that the strength and influence of Southeast Asian oligarchs are largely derived from their deep connections with established political dynasties, as well as their strong relationships with key state institutions and prominent economic groups. These connections not only bolster their political clout but also facilitate their ability to navigate and manipulate the political landscape to their advantage. Despite these oligarchs’ overwhelming influence on national politics—bolstered by deeply ingrained cultural norms and stringent social governance—Southeast Asia has managed to achieve considerable development. This study seeks to provide insights that can influence policy related to oligarchy and economic development while also serving as a direction for future research.